Expression of Multiple engrailed Family Genes in Eyespots of Bicyclus anynana Butterflies Does Not Implicate the Duplication Events in the Evolution of This Morphological Novelty - Banerjee, Tirtha Das; Ramos, Diane; Monteiro, Antónia (Frontiers in Ecology and Evolution, 2020)
Gene duplication events often create genetic redundancy that can either lead to the appearance of pseudogenes or, instead create opportunities for the evolution of novel proteins that can take on new functions. One of the genes which has been widely studied with respect to gene duplication is engrailed (en). En-family proteins are expressed in a morphological novelty, eyespots (in the center and in the outer gold ring), in the African squinting bush brown butterfly Bicyclus anynana, as well as in a more conserved pattern, the posterior compartment of a wing. In the present study, we used whole-genome sequencing and transcriptome data to show the presence of three en-family genes and their differential expression on the pupal wings of B. anynana using in-situ hybridization. The results suggest two duplication events of en-family genes, the first evidence of a two-fold duplication in the Lepidoptera. We propose that all copies initially had posterior wing compartment expression and all copies subsequently gained a novel expression domain associated with eyespot centers. Two copies secondarily lost the posterior compartment expression, and one copy alone gained the outer ring expression domain. By dating the origin of both duplication events, however, we conclude that they predate the origin of eyespots by at least 60 mya, and hence our data does not support the retention of the multiple en gene duplicates in the genome via their involvement with the novel eyespot evolutionary innovation.